STUDY OF SOME IMMUNOLOGICAL PARAMETERS OF IRAQI WOMEN TAKING COMBINED ORAL CONTRACEPTIVES - Eleawi, Sanaa; Hassan, Haider; Katiano , Ann (Iraqi Journal of Science, 2024)
Combined oral contraceptive (COC) caused many immunological abnormalities; our study involved 25 woman taking COC one sheet/mounth and 20 women not use COC (control). The women were examined for acute phase proteins (caeruloplasmin, human alpha antitrypsin (AT) and C-reactive protein), also for antinuclear antibodies (ANA) and body mass Index (BMI).Our results showed significant increase in the level of caerulophasmin, AT and Crp in COC users which are 486.8mg/dL, 1889. 6mg/L and 7.79mg/L respectively compared with the control (non COC users) 355.9mg/dL, 1591.8mg/L and 3.9mg/L. Also results showed high significant increase in ANA level of COC users with a mean of 54.88 u/ml compared with control 36u/ml. BMI showed increase but not significant, in this study it appeared the relationships between ANA, Crp and ANA, and between Caerubplasmin, ANA, and also BMI, Crp with pearson correlation (r) respectively 0.395, 0.373, 0.349, P > 0.01. The increase of acute phase proteins were associated with the incidence of cardiovascular diseases, and the increase in the level of ANA was related to be more susceptibility to autoimmune diseases.